Local tissue factor pathway inhibitor release in the human forearm - Kemme, Michiel J. B.; Burggraaf, Jacobus; Schoemaker, Rik C.; Cohen, Adam F.; Kluft, Cornelis; Chia, Stanley; Webb, David J.; Newby, David E. (Thrombosis and Haemostasis, 2003)
Nineteen healthy men received unilateral brachial artery infusions of either unfractioned heparin (0.3-100 IU/min), saline or the endothelium-dependent vasodilators substance P (2-8 pmol/min) and bradykinin (100-1000 pmol/min), and the endothelium-independent vasodilator sodium nitroprusside (2-8 µg/min). Heparin caused a dose-dependent increase in plasma TFPI concentrations in both arms (ANOVA, p <0.0001). Estimated net forearm TFPI release was 7 ± 16, 29 ± 20 and 138 ± 72 ng/100 mL tissue/min during 10, 30 and 100 IU/min of heparin respectively (ANOVA, p <0.0001). Compared to the systemic circulation, the forearm sensitivity to heparin induced TFPI release was 3.6-fold lower (166 ± 67 ng/IU vs. 596 ± 252 ng/IU: t-test, p = 0.004). Substance P, bradykinin and sodium nitroprusside all caused substantial dose-dependent increases in blood flow (ANOVA, p <0.001 for all) without affecting plasma TFPI concentrations. There are important regional differences in endothelial TFPI release, with the forearm circulation being relatively insensitive to heparin.
Keywords: Tissue factor pathway inhibitor; haemostasis; heparin; substance P; bradykinin